Transesophageal Echocardiography Probe Sheath to Decrease Provider and Environment Contamination. (August 2020) - Markin, Nicholas W.; Cawcutt, Kelly A.; Sayyed, Samer H.; Rupp, Mark E.; Lisco, Steven J.
Abstract : Supplemental Digital Content is available in the text.